The Effect of Macroeconomic Uncertainty on Performance and Strategic Decisions of Companies in the Market - Muh Fuad Randy; Fitri Indah Sari M; Fikri Enggar Lukita; Aldilla Ogies Durri; Mardhan Amran (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to explore the effects of macroeconomic uncertainty on corporate performance and strategic decision-making. By synthesizing existing research, it seeks to understand how firms navigate financial instability, adjust investment strategies, and adopt adaptive frameworks to mitigate the risks associated with economic volatility. Research Method: This study employs a Systematic Literature Review (SLR) approach to analyze empirical findings from multiple industries and economic contexts. The study examines how firms manage risks and capitalize on emerging opportunities in uncertain market conditions by integrating diverse theoretical perspectives, including fundamental options theory, strategic flexibility, and digital transformation. Data from peer-reviewed journal articles and industry reports were analyzed to identify key trends and strategic responses to macroeconomic instability. Results and Discussion: The findings reveal that financial instability, delayed investment decisions, and liquidity constraints are significant challenges that companies face during periods of economic uncertainty. However, firms with diversified portfolios, digital integration, and agile decision-making structures exhibit greater resilience. The study also highlights the role of AI-driven analytics and predictive modeling in enhancing corporate risk management. Corporate governance and risk mitigation strategies are also important in ensuring long-term business sustainability. Implications: This study contributes to academic literature and managerial practice by reinforcing the need for data-driven strategic planning, flexible financial policies, and digital transformation to navigate macroeconomic uncertainty. Future research should investigate sector-specific responses and regional differences to refine corporate adaptation strategies.